Characteristics and Outcome of Surgically Treated Patients with Intradural Extra- and Intramedullary Spinal Metastasis—A Single-Center Retrospective Case Series and Review - Hanna Veronika Salvotti; Alexander Lein; Martin Proescholdt; Nils-Ole Schmidt; Sebastian Siller (Current Oncology, 2024)
Objective: Intradural spinal metastases are considered rare. At present, limited information is available on incidence, surgical management, and outcomes. Methods: We conducted a retrospective patient chart review from 2002 to 2024, identifying all patients surgically treated for intradural spinal metastases. Clinical, surgical and survival data were collected and compared to literature data for patients surgically treated for extradural spinal metastases. Results: A total of 172 patients with spinal metastases were identified with 13 patients meeting inclusion criteria (7.6%). The mean age at diagnosis of intradural spinal metastases was 52 ± 22 years, with diverse primaries including lung (n = 3), breast (n = 2), sarcoma (n = 2), and six unique entities. Intradural spinal metastasis was diagnosed on average of 3.3 years after primary diagnosis. In total, we observed five (38%) intradural-extramedullary and eight (62%) intramedullary metastases, located in the cervical (38.5%), thoracic (46.1%) and lumbar spine (15.4%). The most common preoperative symptoms were pain, sensory changes, and gait ataxia (each 76.9%). Gross total resection was achieved in 54%, and local tumor control in 85%. Postoperatively, 92% exhibited clinical improvement or stability. Most frequent adjuvant treatment was radio- and/or chemotherapy in 85%. The average survival after operation for spinal intradural metastases was 5 months, ranging from 1 month to 120 months. The location of the intradural metastasis in the cervical spine was associated with a significantly more favorable survival outcome (compared to thoracic/lumbar location, p = 0.02). Conclusions: Intradural location of spinal metastases is rare (7.6%). Even so, surgical resection is safe and effective for neurological improvement, and survival appears lower compared to the reported survival of extradural spinal metastases.